The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1603/0022-2585-39.6.870
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Knockdown Resistance Mutations inAnopheles sacharovi(Diptera: Culicidae) and Genetic Distance withAnopheles gambiae(Diptera: Culicidae) Using cDNA Sequencing of the Voltage-Gated Sodium Channel Gene

Abstract: The knockdown resistance (kdr) mutation in the voltage-gated sodium channel gene (VGSCG), an important resistance mechanism against pyrethroids, was studied in Anopheles sacharovi Favre. It was found that the specific primers Agd1 and Agd2 used for polymerase chain reaction (PCR) amplification of Anopheles gambiae Giles VGSCG also amplified this genomic region in An. sacharovi. Comparison of the IIs4-IIs6 domain segments of the gene indicated 70% nucleotides common to both species and a genetic distance of 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…It also has recently been shown in An. sacharovi (Luleyap et al 2002). In Culex, only one study showed leucine to serine substitution resistance in a Chinese strain of Culex pipiens L. mosquitoes in 1999 (Martinez-Torres et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It also has recently been shown in An. sacharovi (Luleyap et al 2002). In Culex, only one study showed leucine to serine substitution resistance in a Chinese strain of Culex pipiens L. mosquitoes in 1999 (Martinez-Torres et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that resistance arose recently is supported by the number of other species showing exactly the same pyrethroid-resistance polymorphisms. The L1014F mutation has been found in Musca domestica (Williamson et al, 1993), Blattela germanica (Dong, 1997), Haematobia irritans (Guerrero et al, 1997), Plutella xylostella (Schuler et al, 1998), Anopheles gambiae (Martinez-Torres et al, 1998), C. pipens (Martinez-Torres et al, 1999a) and Anopheles sacharovi (Luleyap et al, 2002). M918T has been found in M. domestica (Williamson et al, 1996) and H. irritans (Guerrero et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports of kdr mutations co-occurring in A. gambiae (Verhaeghen et al, 2006). L1014S is also present in Anopheles arabiensis (Diabate et al, 2004;Himeidan et al, 2007;Stump et al, 2004;Verhaeghen et al, 2006) and in Anopheles sacharovi from Turkey (Luleyap et al, 2002). With the scaling-up of malaria control efforts using indoor residual spraying with DDT and pyrethroids, and the use of pyrethroid treated bed nets, the continued selection of resistance may compromise control programmes (Czeher et al, 2008;Protopopoff et al, 2008).…”
Section: Introductionmentioning
confidence: 99%